ARBUSCULAR MYCORIRRHIZAL RESPONSE OF FIVE OLIVE (OLEA EUROPAEA L.) INTRODUCED TO AN ARID ZONE IN ALGERIA - Bouabdelli Zahra Robã; Doghbage Abdelghafour; Hafidh Zemour; Walid Soufan; Fathi Abdellatif Belhouadjeb (Natural Resources and Sustainable Development)
This study provides, for the first time, a characterization of the mycorrhizal status of five olive cultivars (Arbequina, Arbosana, Hojiblanca, Picual and Frangivento) introduced in Algeria arid zone. To better understand how these introduced cultivars can adapt to a new environment, their relationship with a native complex of arbuscular mycorrhizal fungi (AMF) was examined in connection with a set of physicochemical soil parameters. Roots and rhizospheric soil were studied. The study area was characterized by alkaline and saline soils, a moderate level of organic matter, high levels of total and active calcium carbonates, low level of available phosphorus and a sandy loamy texture. Our results show the presence of symbiotic arbuscular endomycorrhizal fungi in the five cultivars. Mycorrhizal colonization by AMF revealed that the mycorrhizal frequency (F %) in the root systems reached 100 % for both Arbequina and Hojiblanca varieties. The intensity of mycorrhizal colonization (M %) and the intensity within root fragments (m %) ranged from 3.89 % to 65.96 %, with Hojiblanca showing the lowest and Arbequina the highest values. The abundance of arbuscules in the root fragments (a %) varied between 42.22 % in Frangivento and 68.66 % in Arbequina, while the abundance of arbuscular in the root system (A%) varied from 2.56 to 46.04 % (Hojiblanca and Arbequina respectively). For mycorrhizal frequency (F%), a One-way ANOVA test showed no significant differences between the five cultivars, highly significant differences for arbuscule abundance (a%) and very high significant differences for the M ( %), m ( %) and A ( %). In the rhizospheric soil, 11 species belonging to seven genera, three families, two orders and one class AMF were morphologically identified: Septoglomus constrictum, Septoglomus deserticola, Funneliformis mosseae, Funneliformis fasciculatum, Funneliformis coronatum, Funneliformis geosporum. Rhizophagus sinuosum, Rhizophagus clarus, Claroideoglomus caledonius Gigaspora rosia and Acaulospora bireticulata.